PENERAPAN METODE MIND MAP DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KREATIF MAHASISWA (Penelitian Tindakan Kelas pada Mahasiswa PGMI Semester V STAIN Jurai Siwo Metro) - Siti Annisah (JURNAL TARBIYAH, 2014)
The purpose of this research is to increase the creative thinking skill of students by using the mind map method. It is a classroom action research which is done by two cycles. The subjects of this research are the fifth semester students of PGMI STAIN Jurai Siwo in the academic year of 2012/2013. To get the data of this research, the researcher uses two kinds of instruments; they are test and observation. The test is done to get data of creative thinking skill of student, and observation is done to get data of learning process by using the mind map method. Based on the result of the test, it shows that creative thinking skill of students increase significantly after the mind map method is done. It is suitable with the result of t-test of creative thinking skill of students before and after the mind map method is done. Class A and B have significant value (P-value) 0.000. This significant value (P-value) is less that 0.05. Therefore, Hypothesis state that there is no different means between pre-test and post-test in creative thinking skill of students, it is refused. It means that the means of pre-test and post-test in creative thinking skill of students are different significantly. Thus, the learning by using the mind map method significantly can increase the creative thinking skill of the fifth semester students of PGMI STAIN Jurai Siwo in the academic year of 2012/2013